Angkul-Angkul in Ubud Village and It’s Change - Ayu Ardana Putri; Rini Maulina (Universitas Komputer Indonesia, 2022)
The architecture of buildings in Ubud Village has a peculiarity because it uses the concept of Traditional Balinese Architecture, and the Ubud people mostly work as sculptors, so the building has more carvings or ornaments. One ofthe buildings is angkul-angkul. Angkul-angkul is one of the buildings in the area of a traditional Balinese house that is an access or entrance to the yard of a Balinese Hindu community. With the influence of technological advances, globalization and cultural acculturation, and tourism, the use of angkul-angkul today has begun to shift, both in terms of shape, function, and material. Based on these problems, this study aims to determine the change in the shape and use of angkul-angkul material. Descriptive methods are used to analyze the form of angkul-angkul, with data collection through interviews, observations, and literature studies. The result of the study was that there were variations in new forms and materials in angkul in Banjar Junjungan, Ubud Village. Keywords: Angkul-Angkul; Form; Hindu; Ubud Bali; Design